The Potential of Hot Water Sapan Sungai Aro Thermophilic Bacteria Consortium in Producing Bioethanol - Inayatul Fatia; Irdawati Irdawati; Linda Advinda; Azwir Anhar (Bioscience, 2023)
Biofuel is a potentially renewable alternative fuel in Indonesia. Bioethanol is one example of the most commonly used biofuel. Microorganisms of thermophilic bacteria are known to contribute to the production of bioethanol. Thermophilic bacteria are efficient against high temperature conditions so as to minimize contamination. Production of bioethanol can also use joint culture (consortium). Bioethanol production using a microbial biculture consortium is known to significantly increase the level of bioethanol production. The purpose of this study was to determine the compatibility and to determine the optimum potential of the thermophilic bacterial biculture consortium of Sapan Sungai Aro hot water for bioethanol production. This research is a type of descriptive research. To test the cooperation between consortium isolates of thermophilic bacteria producing bioethanol, a compatibility test was carried out using the disk diffusion method. Then the consortium isolates were fermented in liquid TMM (Thermophilic Minimum Media) medium, the bioethanol content was measured after distillation using a pycnometer. The results of the bacterial compatibility test showed that there was one pair of isolates that were not compatible, namely SSA 8 & SSA 14 due to the presence of a clear zone. On research results. The production of bioethanol by a consortium of thermophilic bacteria gives more optimal results compared to a single isolate. The best thermophilic bacterial biculture consortium from the Sapan Sungai Aro hot spring in producing biofuels is SSA 14 & SSA 16 which is 3.009%.